Evaluations of Morphometric Traits and Body Conformation Indices of Horse Ecotypes Reared in the Highlands of Bale Eco‐Region, Ethiopia - Mesay Guyo; Melaku Tareke; Andualem Tonamo; Diriba Bediye; Girma Defar (Veterinary Medicine and Science)
ABSTRACT Background Morphometric traits discrepancies are associated with production, reproduction, adaptation and behaviours in horses. It also determines the design of harnessing implements, physical injury level and working performance of the native horses. Thus, the study was conducted to evaluate morphometric traits and body conformation indices of horse ecotypes reared across four districts of Bale Zone, Ethiopia. Methods Data of croup height, croup length, hip height, mid‐back height, wither height, hip width, thoracic depth, chest width, body length, sternum height, thorax perimeter and cannon perimeter were measured in 500 horses (294 male and 206 female). Using those traits, 17 body conformation indices were calculated to define the horses for multi‐faceted performances. Results The study revealed that croup height, hip height, wither height, hip width, croup length, body length, thorax perimeter and sternum height were significantly (p < 0.0001) different among the studied districts. The district effect was also significant at p < 0.05 for mid‐back height, thoracic depth, chest width and cannon perimeter. The sexual dimorphism effect was statistically significant for all measured traits; however, females were inferior to males except for cannon perimeter. Body conformation indices of pelvic index, body index, transversal pelvic index and weight were highly significant (p < 0.0001) among the studied districts. The sex dimorphism effect was significant (p < 0.001) for dactyl‐costal index, pelvic index, longitudinal pelvic index, transversal pelvic index, weight, tare index 1 (trot or gallop), tare index 2 (walk) and riding comfort degree, while non‐significant (p > 0.05) for the remaining indices. The studied horses were classified as mediline, elipometric, light, small and suitable riding ecotypes with a medium‐conforming body structure and good capacity for carrying loads on carts and backs for functional effectiveness. The correlations of body conformation indices ranged from very high to low, with positive and negative associations for functional capabilities. Conclusion Therefore, selection for improvement needs to rank morphometric traits and body conformation indices in correlation to developing racing and modern sport horses in the highlands of the Bale eco‐regions. Further, molecular studies will be essential to determine whether the predominated phenotypic multiplicity is genetic or environmentally progressed.